Eva and the lost pony - Elliott, Rebecca (Elliott, Rebecca. Owl diaries, 2018)
Eva decides that warning all the animals in the forest about the approaching storm is a perfect project to prove herself worthy of taking the Owl Oath, but when she stops to help a lost pony and they get caught in the storm, they have to take shelter in a cave, and end up helping each other to stay brave.